CPG-based control system for flexible snake robot locomotion - Khan, Md. Raisuddin; Billah, Md. Masum (2014)
Central Pattern Generator (GPG) is an online motion generation system that reduces the memory size of the controller. Past control systems were used predetermined motion data to control snake robot. CPG system makes a solution to overcome such kind of predetermined data. Snake robots are generally consist of serially connected multiple links. An intervallic function is used to model the bending of each link of the snake robot. CPG can generate this intervallic function. CPG generates the recurring signal from the input signal by using its internal biological oscillators. Each of the links of the flexible snake robot performs bending to produce motion using proposed neural oscillator of CPG system. Performance of CPG control system is established from the obtained simulation results and planned in snake robot application. This research shows a novel algorithm to generate online serpentine motion generation using CPG for even terrain locomotion provided that snakes are constructed with flexible links.